Enforcement notice as a form of protection of the right to a minimum hourly rate - Paroń, Łukasz (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The introduction of a minimum hourly rate for individuals working under civil law contracts represented a significant milestone in improving the legal protection standards for this group of employees. As part of the change, the State Labour Inspectorate has been granted the authority to monitor this issue and take legal action by issuing an enforcement notice. Rather interesting, this solution warrants analysis in comparison with another measure employed by state labour inspectors in the form of a payment order. Comparing these legal measures is justified due to their similar purpose of guaranteeing payment of wages to remunerated employees.